Modern aspects of parvovirus B19 infection in children - L. V. Gorbacheva; V. G. Pyaternina; N. S. Tian; O. V. Goleva; I. V. Babachenko (Детские инфекции (Москва))
Purpose: to establish clinical and laboratory features of parvovirus B19 infection (PVI) in children at the present stage.Materials and methods: a retrospective analysis of hospitalization records from 01.01.2023 to 01.07.2023 was conducted at Pediatric Research and Clinical Center for Infectious Diseases. The study included 101 children aged from 1 month to 17 years old inclusive who had confirmed PVI (positive for specific antibody IgM by enzyme immunoassay (ELISA) and/or viral DNA detected in the blood using polymerase chain reaction (PCR).Results: most cases of PVI were reported from April to June (76%). Children were admitted to the hospital mainly in the early stages of the illness (4.4 ± 0.4 days). The age structure was dominated by school-age children (64%), patients of early and preschool age were hospitalized with the same frequency (16% and 17%, respectively). Infants were admitted in isolated cases (3%). PVI was mild to moderate in 97% of patients. 88% of children had a fever of varying intensity. The main clinical manifestations were rhinitis (68%) and exanthema (92%). The most common were spotted (39%), spotted papular (33%) and hemorrhagic rash (20%). The «lace» nature of the rash, which often described in literature, was observed in 8% of patients. The characteristic symptom of a «slap in the face» was recorded in only 40% of children. There were no significant changes red blood cell production or shifts in the white blood cell count in the complete blood count. When evaluating the results of the etiological examination, it was found that in the first three days of the illness, the majority of positive results were by PCR, which provided a decryption in 97% of cases. The significance of this technique has decreased over time, and by the eighth day of the illness the most useful serological test has been ELISA, which determines IgM and IgG specific antibodies. In 35% of children, the diagnosis was confirmed using a combination of methods, and IgM and IgG antibodies were detected alongside DNA parvovirus B19. The determination of specific IgG on 4.5 ± 0.7 day of illness in 34% of cases does not exclude the reactivation of persistent PVI, which confirms the relevance of further researches.